Bipartite Synchronization of Heterogeneous Signed Networks with Distributed Impulsive Control - Guizhen Feng; Jian Ding; Jinde Cao; Qingqing Cao (Complexity)
This study investigates the bipartite synchronization of heterogeneous signed networks with distributed impulsive control. Leader-follower bipartite synchronization within a nonzero error bound is analyzed when the average impulsive interval is Ta<∞ or Ta=∞. Some sufficient conditions to achieve the bipartite quasi-synchronization are presented, and the synchronization error level is estimated by the specific mathematical expression. The correctness of the theoretical results is verified by numerical examples.